The prevalence and severity of temporomandibular disorder (TMD) among female dental students in Riyadh, Saudi Arabia - Alhanouf Abdulrahman AlHussaini; Lina Hassan AlHudithy; Mashael Abdulaziz AlHadlaq; Njood Fahad AlAzzam; Noor Walid Abahussain; Shamma Abdullah AlDukhiel; May Ahmad AlSenani; Loulwah Khalid AlOthman (Elsevier, 2019)
Introduction: Temporomandibular disorders are the second most common musculoskeletal conditions that cause pain and disability. The pathogenesis of TMD is multifactorial, involving biological, psychological and behavioral factors. Several studies suggested that stress and TMD are related, according to (Korszun et al., 2017) that indicated "Patients appearing for treatment with chronic facial pain show a high comorbidity with other stress-associated syndromes".TMD prevalence is 20-30% of adult populations, and more common in females. TMD can be screened by clinical examinations, or by using "Fonseca's Anamnestic Index" (FAI). Methodology: Anonymous electronic questioner was distributed through social media to several female dental colleges in Riyadh. The questioner included two parts, first one to assess the severity and signs and symptoms of TMD using "Fonseca's anamnestic index" (FAI). The second part to measure anxiety level using "Zung Anxiety Self-Assessment Scale" (SAS). The analysis was done using SPSS, applying Chi square tests. Results: The cross-tabulation of the academic year with (FAI) resulted in a P-value of 0.405 indicating no significance. The cross-tabulation of the academic year with (SAS) resulted in a P-value of 0.093 indicating a slight significance. The cross-tabulation of Fonseca's index results with Zung's anxiety resulted in a P-value of 0.000 indicating a high significance. Conclusion: Our results showed that anxiety is highly related to TMD and we concluded that 62.8% of female dental students has anxiety of different levels.